COST TREND: MEANING AND IMPORTANCE OF COST TREND IN PUBLIC ENTERPRISES (American Journal of Technology and Applied Sciences, 2022)
The specialization large scale production, international marketing and increasing competition make it necessary not only to keep the cost under control but to reduce the cost to the maximum possible extent. To stand in the keen competition in the international markets makes it very important that the costs of exports are kept at the minimum and uninterrupted and efforts are made to locate new areas of cost control and reduction. At present when the world is moving at a fast rate only those concerns can survive who are continuously striving for improving their efficiency and effectiveness, and adding the value through cost reduction and bettering the product. A proper analysis f cost may enable the management to find sources of waste and cost as-elations. The analysis of cost provides the basic information on the basis of which top management may effectively control and reduce the cost.